Creative Problem Solving sebagai Media Pengembangan Makanan (Studi Kasus pada Mata Kuliah Introduction to Culinary Business Environment di Culinary Business Department Universitas Ciputra Surabaya) - Michael Ricky Sondak (Journal of Tourism Destination and Attraction, 2014)
Introduction to Culinary Business Environment is a course that is based on a real project with real problems experienced by students. Students are expected to be able to understand and professionals of the food product, bakery & pastry terminology, preparation, seasoning and ingredients used, cooking methods and manner of presentation. Live Entertainment Project will be held by combining the comprehensive, synthesis and evaluation with an application to the project. Students are expected to have some successful indicators to be achieved and learning experiences. Classroom action research is used on this research. This research is about how to implement the creative problem solving methods by The Herrmann Model as a tool of developing a creative way of food.